The adoption paradox: Exploring the role of ethnicity, deprivation, and co-ethnic density in care proceedings in England - Bachar Alrouh; Mariam Abouelenin; Stefanie Doebler; Karen Broadhurst (International Journal of Population Data Science, 2023)
The study objectives were to (1) examine the association between children’s ethnicity and final legal orders at the end of family care proceedings (section 31 of the 1989 Children Act), and (2) test whether residential context, such as co-ethnic density and area-level deprivation, moderates this association.